Implementasi Metode Drill dengan Permainan Berbasis Kearifan Lokal Jawa untuk Konsep Perkalian-Pembagian Siswa Sekolah Dasar - Erna Noviyanti (Action Research Journal, 2022)
This study aims to find out how to implement the drill method with games based on Javanese local wisdom for the concept of multiplication-division of elementary school students. This research uses descriptive qualitative method with literature study technique. Data collection techniques by looking through articles, journals, proceedings, observing learning activities in class, interviews with colleagues and students, and quick counting tests on the concepts of multiplication and division. This implementation requires consistency and readiness of students in learning to be proficient in fast counting. They can get to know the local Javanese culture of the region which is packaged in the form of games and practice quick counting skills on the concepts of multiplication and division which are expected to make it easier for students to learn the next material. This literature study can be used as a basis for applied learning and for further research.